Effect of Hexa Boron Nitride and REO Addition on Wear and Corrosion Behavior of Hard-Facing on Mild Steel - Singh, Sikander Pal (My University, 2018)
Hard-facing technique improves the mechanical properties of material as well as chemical properties also. It increases the service life of metal. Use of hard-facing in many wide applications like concrete mixer, rock crusher, crane jaws, sugarcane rollers etc. This technique improves the wear resistant and corrosion resistant of material. It improves the hardness also. This study was revealed the effect of hexa boron nitride and lanthanum oxide additive on wear resistance and corrosion resistance of hard-facing on mild steel of grade E-250, which was developed by an manual arc welding process. Wear test performed by pin-on-disc machine. Microstructure and size of grains were studied by EBSD (Electron backscatter diffraction). Corrosion test was performed by salt spray chamber. Experiment duration in salt spray chamber was 120 hours. Hardness of the element on hard-facing layer was measured by vickerhardness test. Four samples were prepared sample N (addition of HBN), sample A (addition of no element), sample LN (addition of lanthanum oxide and HBN) and sample L(addition of lanthanum oxide). The results were shown that with addition of hexa boron nitride hardness of weld layer was enhanced and with addition of lanthanum hardness was decreased. Hardness in case of HBN expanded by 20 % but lanthanum reduced the hardness by 2 % as compared to sample A. Combination of HBN and lanthanum oxide enhanced the hardness by 14.5 % as compared to that sample in which no element was added. Grain size with addition of hexa boron nitride reduced to 3.78214±1.22594 microns. Lanthanum oxide increased the size of grains to 17.825±2.5877 microns. Grains size of reference sample A in which no element was added was 10.5847±2.59363 microns. In combination of both the HBN and La2o3 reduced the grains size which was 5.63378±1.55312 microns. In corrosion experiment, addition of HBN increased the corrosion rate. 60% area of the weld bead of sample got corrosion in which HBN was added. HBN reduced the corrosion resistance. Lanthanum oxide enhanced the corrosion resistance. Only 15 % area of weld bead was corroded of sample L in La2o3 was added. In the combination of both HBN and lanthanum oxide 15 % area of weld bead corroded. Wear resistance of HBN was good as compared to reference sample A. Lanthanum oxide and HBN were shown good wear resistance than reference sample A because of less weight loss. Sample A got 0.014 g weight loss at 49.05 N load and 6000 m sliding distance. Sample N got 0.011g weight loss at 49.05 N load and 4200 m sliding distance. Sample LN got same weight loss as sample N at same loading condition and same sliding distance.
Master of Engineering- Production
Keywords: EBSD; Corrosion; Lanthanum